(untitled) (Bangladesh Journal of Agricultural Research, 2026)
Mixed cropping practices can help farmers meet their different types of daily needs because mustard can be used as edible oil, whereas field peas may be consumed as legume food. The field experiments were carried out at a farmer’s field in South Lemua, MLT site, Feni (AEZ 19a), during the Rabi seasons of 2015-16 and 2017-18 to find out the performance of field pea as a mixed crop with mustard. The treatment combinations were T1 = Sole field pea (100%) @ seed rate 50 kg ha-1, T2 = Sole mustard (100%) @ seed rate 7 kg ha-1, T3 = field pea (90%) + mustard (10%), T4 = Field pea (80%) + mustard (20%), and T5 = Field pea (70%) + mustard (30%). A field pea var. BARI Motor-1 and a mustard var. BARI Sarisha-14 were used . The trial was conducted in a randomized complete block design with 6 dispersed replications. . The seed yield of field pea decreased with the increase of mustard population and the yield of mustard decreased with the increase of field pea population in the mixed cropped situation. All the mixed cropping combinations showed superiority over sole cropping in terms of gross margin, benefit cost ratio (BCR), and field pea equivalent yield (FEY). The highest field pea equivalent yields were 1646 kg ha-1 in 2015-16 and 1576 kg ha-1 in 2017-18, respectivelyin the treatment combination of field pea (80%) and mustard (20%). The lowest FEYs were observed at 1326 kg ha-1 in T2 during 2015–16 and 1296 kg ha-1 in T1 during 2017–18. The highest gross margins (Tk. 49280 ha-1 in 2015-16 and Tk. 44854 ha-1 in 2017-18) as well as BCR (2.45 in 2015-16 and 2.32 in 2017-18) were obtained from T4 treatment. In 2015–16, T2 provided the lowest gross margin (Tk. 31980 ha-1) and BCR (1.93), but in 2017–18, T1 yielded the lowest gross margin (Tk. 32515 ha-1) and BCR (2.00). More profitable mixed crops combinations should be explored in future research. Bangladesh J. Agril. Res. 47(4): 371-381, December 2022